Outside director compensation in German public family firms : an empirical analysis - Engel, Pascal (Familienunternehmen und KMU, 2015)
Pascal Engel investigates how outside directors are incentivized in family firms that are publicly listed but still partly owned by members of the founding family. Owning families significantly influence their firms' corporate conduct with their own set of goals, sometimes in conflict with economically driven goals of the capital markets. The author analyzes how family shareholders exert their influence on compensation schemes of outside directors who have the difficult task to protect the interests of family and non-family shareholders. This book provides insights on current approaches of defining a compensation scheme that attracts qualified outside directors but concurrently reflects respective shareholders' preferences.  Contents Research on Family Firms Outside Directors' Pay Level Voluntary Disclosure of Outside Directors' Compensation Outside Directors' Pay Mix  Target Groups Researchers and students in the fields of compensation, corporate governance, and family business research Shareholders, executives, and outside directors of public family firms as well as analysts and compensation consultants  The Author Dr. Pascal Engel wrote his dissertation under the supervision of Prof. Dr. Andreas Hack at the Institute for Family Businesses at WHU - Otto Beisheim School of Management, Vallendar.  About the Editors The series Familienunternehmen und KMU is edited by Prof. Dr. Andreas Hack, Prof. Dr. Andrea Calabrò, Prof. Dr. Hermann Frank, Prof. Franz W. Kellermanns Ph.D. and Prof. Dr. Thomas Zellweger.